منهجية الامام الحسن بن علي (عليهما السلام) السياسية في الحكم - صالح عمار باسم; صالح حيزومه شاكر رشيد; علي عبد العزيز كاظم; داود ساجدة علاوي; محمد ايمان جاسم; فرحان انسام عامر (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
For Imam al-Hassan, politics represented a complete approach to life, and it included all its aspects. He established a complete system of belief, legislated for them a complete system of morals, legislated for them a complete system of worship, and prescribed for them multiple systems of dealings that cover all aspects of life. Examining the results of matters before making a decision. Thinking about stopping the war is nothing but a decision issued by a divine figure who receives its rulings from the inspiration of the Muhammadan divine law, and it contains dreams, wisdom and civility what the other side does not possess. The research confirmed that the dream of Imam al-Hassan was not out of humiliation or lethargy, but rather from the standpoint of strength and courage that the Imam possessed, may God bless him. His dream was accompanied by courage and power associated with intellectual freedom, and the Imam believed that the nation’s interest requires a reversal of the war decision in light of exceptional and difficult circumstances that the Imam witnessed at the time, which was mentioned by history. The right of the Creator’s law belongs to him, the Almighty. On the contrary, the dream of Imam al-Hassan was not out of humiliation or lethargy, but rather out of strength and courage that he possessed. The research clarified that negotiations with Muawiyah are not considered reconciliation, concession, or weakness and dishonor by the Imam, may God’s peace be upon him.